Developed multi-objective grey wolf optimizer with fuzzy logic decision-making tool for direction overcurrent relays coordination - Korashy, Ahmed; Kamel, Salah; Nasrat, Loai; Jurado, Francisco (Soft computing (Berlin, Germany), 2020)
This paper proposes a new methodology for solving the coordination problem of DOCRs based on multi-objective grey wolf optimizer and fuzzy logic decision-making. In addition to the conventional objective function, a new objective function which aims to minimize the discrimination time between primary and backup relays is proposed. Moreover, the conventional objective function related to minimizing the total operating time of primary and backup relays is considered. The feasibility and performance of the proposed methodology for solving the coordination problem of DOCRs are investigated using two different systems (8-bus system and IEEE-30 bus system). The proposed methodology is compared with other reported methods. The results prove the viability and effectiveness of the proposed methodology to solve the DOCR coordination problem without any miscoordination between primary and backup relays.